The Impact of Problem-Posing Strategies on Differentiated Natural Science Instruction for Slow Learners - Nisa, Arifatun Khoirun; Maryani, Ika (The Indonesian Institute of Science and Technology Research, 2025)
This study aims to explore the implementation of differentiated natural science instruction for slow learner students at Giwangan Elementary School (a public school in Yogyakarta) as part of an effort to promote an inclusive and adaptive educational environment. A qualitative research approach was employed, involving classroom observations, semi-structured interviews with teachers and support staff, and document analysis to gather comprehensive data on instructional practices. The results indicate that teachers conducted diagnostic assessments to determine individual learning needs, which guided the development of tailored teaching modules utilizing visual media such as images, educational videos, and flashcards. Instruction was delivered through personalized and interactive strategies, supported by classroom and shadow teachers. Evaluations were adapted accordingly, with standard written assessments for regular students and image-based tests for slow learner students. The findings suggest that the success of differentiated instruction is closely tied to teacher competency, the involvement of Special Assistant Teachers, and the principal’s inclusive policies. However, the study also identifies key challenges, including limited preparation time for lesson adaptation, a shortage of support personnel, and budgetary limitations that affect access to adequate learning resources. In conclusion, differentiated learning strategies can effectively support slow learner students when implemented collaboratively and systematically. The implication of this study is the need for increased institutional support, targeted teacher training, and policy reinforcement to sustain inclusive practices and ensure equitable learning outcomes for all students.